We need to work differently in a crisis: peer-professional leadership to redesign physicians' work. Issue 2 (4th August 2021) - Woiceshyn, Jaana; Huq, Jo-Louise; Kannappan, Sunand; Fabreau, Gabriel; Minty, Evan; Pendharkar, Sachin; Bharwani, Aleem
Abstract : Background: Understanding physician leadership is critical during pandemics and other health crises when formal organisational leaders may be unable to respond expeditiously. This study examined how physician leaders managed to quickly design a new model for acute-care physicians' work, adopted across four large hospitals in a public health authority in Canada during the COVID-19 pandemic. Methods: The research employed a qualitative case study methodology, with inductive analysis of interview transcripts and documents. Shortly after a physician work model redesign, we interviewed key informants: the physician leaders and others who participated in or supported the model's development. Participants were chosen based on their leadership role and through snowballing. All those who were approached agreed to participate. Results: A process model describes leadership actions during four phases of work model development (priming, early planning, readying for operations and transition). These actions were: (1) recognising the threat, (2) committing to action, (3) forming and organising, (4) building and relying on relationships, (5) developing supporting processes and (6) designing functions and structure. We offer three additional contributions to knowledge about leadership in a time of crisis: (1) leveraging peer-professional leadership to initiate, formalise and organise change processes, (2) designing a new work model on existing and emerging evidence and (3) building and relying on relationships to unify various actors. Conclusions: The model of peer-professional leadership can deepen understanding of how to lead professionals. Our findings could assist peer-professional and organisational leaders to encourage quick redesign of professionals' work in response to new phases of the COVID-19 pandemic or other crises.